Service-oriented software system engineering : - Stojanovic, Zoran (IDEA Group Publishing, 2005)
Service-oriented software system engineering: challenges and practices : challenges and practices provides a comprehensive view of SOSE through a number of different per-spectives. Some of those perspectives include: service-based con-cepts, modeling and documentation, service discovery and com-position, service-oriented architecture, model-driven development of service-oriented applications, service security and service-ori-entation in mobile settings. It provides readers with an in-depth knowledge of the main challenges and practices in the exciting, new world of service-oriented software engineering. Addressing both technical and organizational aspects of this new field, this book offers a balance making it valuable to a variety of readers, including IT architects, developers, managers and analysts.